Resistencia a la compresión y flexión de ladrillos de arcilla artesanales de Chambo con adición de polvo de vidrio reciclado - Dávalos Castelo, Henry Francisco (2022)
The following document describes the main findings of resistance when implementing recycled glass powder as an ingredient in the production of artisanal bricks in Chambo canton. For this, we proceeded with the characterization of the raw material of the brick (soil and ash), later the manufacture of bricks with the addition of glass powder (PV) is carried out, using the artisanal procedure in its elaboration, and changing only the addition of glass powder to the mixture. The results show that the soil used as raw material, when classified using the SUCS methodology, corresponds to a well-graded sand with silt (SW-SM), results that contrast with the belief that this material is poor quality clay. Glass powder modified bricks show up to 240% compressive strength and 220% flexural strength capability respect traditional bricks when using 12% to 16% glass powder dosage in the mixture. In addition, both traditional and modified bricks have an absorption percentage between 25% and 26%. For the procedures, as well as the interpretation and contrast of the results, this research is based on the guidelines established in the corresponding regulations established by the Ecuadorian Institute of Standardization INEN.